Peningkatan Hasil Belajar Siswa Sekolah Dasar melalui Model Pembelajaran Talking Stick - Yulia Sugina; Kasmantoni Kasmantoni (Jurnal Indonesia Pendidikan Profesi Guru, 2025)
Background: The success or failure of learning can be evaluated from both the learning process and the outcomes achieved. In the context of Islamic Religious Education (PAI), student engagement and active participation are crucial to achieving meaningful learning. Objective: This study aims to determine the effectiveness of the talking stick learning model in improving the learning outcomes of Islamic Religious Education among fourth-grade students at SD Muhammadiyah Pasar Manna, South Bengkulu. Method: This research is a Classroom Action Research (CAR) conducted in 2023 at SD Muhammadiyah Pasar Manna. The study involved a sample of 20 fourth-grade students. Primary and secondary data were used in the research, with data collected through tests, observations, and questionnaires. The data were analyzed using descriptive techniques based on learning outcomes, observation, and reflection. Result: The findings show that the application of the talking stick learning model has a positive impact on students' learning motivation and outcomes in Islamic Religious Education. Students demonstrated increased engagement and improved academic performance through the interactive learning process facilitated by this method. Conclusion: The talking stick learning model is effective in enhancing both motivation and achievement in PAI subjects for elementary school students, supporting more active and student-centered learning. Contribution: This study provides practical insight for educators, especially in Islamic Religious Education, by highlighting an alternative interactive method that can improve student participation and academic success. It serves as a reference for implementing active learning strategies in religious education at the elementary level.